KONTRIBUSI KEPEMIMPINAN DAN KERJASAMA TIM TERHADAP KEPUASAN KINERJA DALAM PENDIDIKAN ISLAM - Istifadah, Istifadah; Sukarman, Sukarman; Mukarom, Muh; Khoiriyah, Ida Nur Lailatul (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
In the world of education, performance satisfaction is an important factor that can affect the quality of education in terms of the quality of learning and development of students. This study at Madrasah Ibtidaiyah (MI) Sultan Fatah Demak aims to determine the contribution of leadership and teamwork to the satisfaction of Islamic education performance. This study uses a qualitative method with observations on the leadership of the madrasah principal and conducting comprehensive interviews with the principal and teachers. The results of the study indicate that there is a contribution related to leadership and teamwork to the satisfaction of performance in Islamic education at MI Sultan Fatah. However, in carrying out tasks in teamwork, there are some jobs that are not evenly distributed, making some teachers feel heavier, so that evaluation and discussion are needed regarding the distribution of tasks evenly so that the performance given by the teacher can be optimal.